Dampak Media Sosial terhadap Berpikir Kritis Anak Usia Dini: Studi Komparatif Lintas Budaya - Lubis, Maesaroh; Harahap, Sahrona (NANAEKE: Indonesian Journal of Early Childhood Education, 2024)
The study aims to analyze the impact of social media on children's ability to think critically in different global cultures, given the increasing dominance of the social media role in everyday life. Using a qualitative approach and exploring a wide range of relevant literature, the study examines how social media affects critical thinking skills, including access to information, resource evaluation, analysis, decision-making, and problem-solving. This study was carried out from three cultures in Indonesia such as the Batak, Sunda, and Java tribes, then made a distinction with several cultures of the United States, Britain, South Korea, Australia, and Europe revealing a consistent negative impact although varying according to local cultural values. The findings of this study confirm the need to develop a digital education strategy that considers the cultural context to enhance children's critical thinking skills in the digital age.